Sperm Morphology Analysis with CNN based algorithms - Savkay, O. Levent; Cesur, Evren; Yalcin, Mustak E.; Tavsanoglu, Vedat (2014 14th International Workshop on Cellular Nanoscale Networks and their Applications (CNNA), 2014)
In this paper Morphological Analysis part of our proposed computer-aided sperm analysis system (CASA) is simulated and the results beside the algorithm steps are presented. The morphology analysis is simply dealing with shape of the sperms and extracting the shape characteristics in medical parameters. The characteristics are obtained by image processing algorithms which utilizes Cellular Nanoscale Network (CNN) based and spatial image processing blocks. The following calculation of medical parameters are obtained from the outputs of image processing blocks. The algorithm is so designed to adapt the final SoC architecture such as Xilinx Zynq7000 device.